Хелмінське земське та хелмінське сільське право - Дмитришин, Юрій Любомирович; Дмитришин, Юрий Любомирович; Dmitrishin, Jurij (Одеса : Юрид. л-ра, 2014)
In the article the formation and development of khelmno zemske and khelmno rural law is analyzed. The structure of khelmno zemske and khelmno rural law is given. Many of its norms are taken from the Polish and Hungarian zemske law. Establishment and structure of zemski courts are described.
Дмитришин Ю. Л. Хелмінське земське та хелмінське сільське право / Ю. Л. Дмитришин // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 68-73.
Keywords: хелмінське право; земське право; сільське право; земський суд; хелминское право; земское право; сельское право; земской суд; khelmno law; zemske law; rural law; zemskiy court